PERSEPSI MAHASISWA TERHADAP PROJECT-BASED LEARNING PADA PROGRAM STUDI PARIWISATA - I Putu Edi Sutrisna; Anak Agung Mahendra Kusuma (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2022)
Project-based learning is one of the learning models that is currently a topic of discussion in educational field in Indonesia. Looking at the latest results related to the implementation of this project-based learning model, it can be seen that this model is proven to be effective and increase the expected learning outcomes. However, it is proven that the effectiveness those studies on project-based learning only focused on improving the learning outcomes but did not pay attention to how the participants perceive this project-based learning. Therefore, through qualitative research using a phenomenological approach, this study aims to analyze how the perceptions of students in the Cultural and Religious Tourism Study Program of STAHN Mpu Kuturan Singaraja whic have implemented this project-based learning model. From the results of the analysis that has been carried out, it was found that students have positive perception towards project-based learning, where the learning is felt to be fun and able to provide real experiences before students actually go directly into the tourism industry.